Procure, Bank, Release: Carbon Removal Certificate Reserves to Manage Carbon Prices on the Path to Net-Zero - Wilfried Rickels; Roland Rothenstein; Felix Schenuit; Mathias Fridahl (Energy Research & Social Science, 2022)
The European Union cap-and-trade emissions trading system (EU ETS) faces two challenges in the context of the European Green Deal. First, to meet the Paris temperature target, emissions in the energy and industrial sectors must fall to net-zero and then even become net-negative. Second, there is a concern that excessive CO2 price spikes and volatility on this path will jeopardize the political acceptance and support for emissions trading as a climate policy instrument. Conditional supply of carbon removal credits (CRCs) to support dynamic carbon price caps would make it possible to stabilize the market in the transition from positive to net-negative emissions trading while keeping the net-emissions path unchanged. CRCs would be assigned for carbon removal achieved for example with methods like Direct Air Carbon Capture and Storage or Bioenergy with Carbon Capture and Storage and would be used by companies under the EU ETS to compensate for their emissions. However, we suggest that there would be no direct exchange between emitting companies under the EU ETS and carbon removal companies, i.e., the demand and supply side of CRCs, during an initial phase. Instead, we suggest assigning an institutional mandate to for example a carbon central bank (CCB) to organize the supply of CRCs. Under this mandate, carbon removal would be procured, would be translated into a corresponding number of CRCs, and a fraction of it could be auctioned to the market at a later point in time, provided that market prices exceed a certain (dynamic) price cap.
Keywords: 330; European emissions trading; Carbon pricing; Carbon dioxide removal methods; EU climate policy